Knockdown of PPARδ Induces VEGFA-Mediated Angiogenesis via Interaction With ERO1A in Human Colorectal Cancer - Luo, Wenjun; He, Diao; Zhang, Jianhao; Ma, Zida; Chen, Keling; lv, Zhaoying; Fan, Chuanwen; Yang, Lie; Li, Yuan; Zhou, Zongguang (Frontiers in Oncology, 2021)
Angiogenesis is an important mechanism underlying the development and metastasis of colorectal cancer (CRC) and has emerged as a therapeutic target for metastatic CRC (mCRC). Our recent studies found that Peroxisome proliferator-activated receptor β/δ/D (PPARδ) regulates vascular endothelial growth factor A(VEGFA) secretion and the sensitivity to bevacizumab in CRC. However, its exact effect and underlying mechanisms remain unidentified. In this study, we showed that PPARδ expression was inversely associated with the microvascular density in human CRC tissues. Knockdown of PPARδ enhanced VEGFA expression in HCT116 cells and HUVEC angiogenesis in vitro; these phenomena were replicated in the experimental in vivo studies. By tandem mass tag (TMT)-labeling proteomics and chromatin immunoprecipitation sequencing (ChIP-seq) analyses, endoplasmic reticulum oxidoreductase 1 alpha (ERO1A) was screened and predicted as a target gene of PPARδ. This was verified by exploring the effect of coregulation of PPARδ and ERO1A on the VEGFA expression in HCT116 cells. The results revealed that PPARδ induced VEGFA by interacting with ERO1A. In conclusion, our results suggest that knockdown of PPARδ can promote CRC angiogenesis by upregulating VEGFA through ERO1A. This pathway may be a potential target for mCRC treatment.